2004
DOI: 10.1258/1357633042614212
|View full text |Cite
|
Sign up to set email alerts
|

The use of telemedicine in the management of vascular surgical referrals

Abstract: We have performed a feasibility study of telemedicine as an alternative to conventional outpatient appointments for the making of diagnostic and management decisions for patients referred for vascular surgery. Twenty-two sequential patients referred by a single general practice to a vascular centre were offered a telemedicine clinic appointment as an alternative to a conventional hospital outpatient appointment. A referral pro forma and digital photograph (where appropriate) were transmitted in advance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Studies that reported telemedicine for preoperative or diagnostic processes, such as Lee, et al, reported 100% agreement between the telemedicine technology and the on-site preoperative diagnostic results ( 15 ). Hands, et al referred patients to the vascular surgery clinic via telemedicine and found the introduction of alternative management plans to be beneficial for consultants and patients ( 16 ). Demartines et al discussed the accuracy of judging organ structure and function before digestive or endocrine surgery ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that reported telemedicine for preoperative or diagnostic processes, such as Lee, et al, reported 100% agreement between the telemedicine technology and the on-site preoperative diagnostic results ( 15 ). Hands, et al referred patients to the vascular surgery clinic via telemedicine and found the introduction of alternative management plans to be beneficial for consultants and patients ( 16 ). Demartines et al discussed the accuracy of judging organ structure and function before digestive or endocrine surgery ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to Martínez-Ramos et al telemedicine helped physicians assess local complications and avoid unnecessary hospital visits ( 25 ). Regarding preoperative diagnosis, telemedicine via internet-enabled computers was beneficial in two studies ( 9 , 16 ). As for postoperative care, videoconferencing and digital cameras provided an accurate diagnosis and treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…In another instance, videoconferencing was used for the management of patients at home after carotid endarterectomy procedures, which allowed for early patient discharge 61 . Preoperative management and referral of vascular surgery candidates using TM has also been tested, involving live consultations with off‐site specialists, however, this usually requires patients to be physically present at locations which have access to trained staff and diagnostic facilities 62‐64 …”
Section: Introduction To Covid‐19mentioning
confidence: 99%
“…2 Furthermore, many institutions have expanded telehealth capabilities into several surgical fields including vascular, bariatric, maxillofacial, thoracic, and transplant surgery. [3][4][5][6][7] Several benefits of telehealth have been previously described, including high patient and provider satisfaction and reduced barriers related to travel. 8 With the expansion of Medicare coverage to now include telehealth services during the COVID-19 pandemic, there is an anticipated surge in usage as millions of Americans now have insurance coverage for such programs.…”
mentioning
confidence: 99%